Right-Sided Intrarenal Splenosis Mimicking a Renal Carcinoma - Jay B. Page; Dean L. Lenz; Carson Wong (The Scientific World Journal)
We describe a patient who underwent nephrectomy for an enhancing right renal mass that was subsequently pathologically confirmed as right renal splenosis. Since renal splenosis is quite rare and has previously been reported only in the left kidney, we did not consider splenosis in our differential diagnosis during the evaluation of the renal mass. Magnetic resonance imaging, as well as radionucleotide scan using 99mTc-labelled red blood cells, has been utilized for identifying ectopic splenic tissue. An elevated index of suspicion must be present in patients with a history of splenectomy or traumatic splenic rupture to avoid undue nephrectomy.